2022
DOI: 10.1038/s41598-022-06989-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific 3D-printed shelf implant for the treatment of hip dysplasia tested in an experimental animal pilot in canines

Abstract: The concept of a novel patient-specific 3D-printed shelf implant should be evaluated in a relevant large animal model with hip dysplasia. Therefore, three dogs with radiographic bilateral hip dysplasia and a positive subluxation test underwent unilateral acetabular augmentation with a 3D-printed dog-specific titanium implant. The contralateral side served as control. The implants were designed on CT-based pelvic bone segmentations and extended the dysplastic acetabular rim to increase the weight bearing surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…The titanium implants were designed at University Medical Centre Utrecht from preoperative CT images of the complete pelvis as described by Willemsen et al ( 24 ), using Mimics (version 24, Materialise, Leuven, Belgium) for segmentation of the DICOM files and 3-Matic (version 16, Materialise, Leuven, Belgium) for implant design. Like the implants described by Willemsen et al ( 24 , 25 ), the implants consisted of two subsections as follows: the implant–bone interface or attachment part and the acetabular rim extension part ( Figure 2 ). The attachment part was designed with a porous inner shell (1 mm sized Dode-Medium unit cell) and incorporated four screw holes and an additional ventral ilium flange for ease of positioning.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The titanium implants were designed at University Medical Centre Utrecht from preoperative CT images of the complete pelvis as described by Willemsen et al ( 24 ), using Mimics (version 24, Materialise, Leuven, Belgium) for segmentation of the DICOM files and 3-Matic (version 16, Materialise, Leuven, Belgium) for implant design. Like the implants described by Willemsen et al ( 24 , 25 ), the implants consisted of two subsections as follows: the implant–bone interface or attachment part and the acetabular rim extension part ( Figure 2 ). The attachment part was designed with a porous inner shell (1 mm sized Dode-Medium unit cell) and incorporated four screw holes and an additional ventral ilium flange for ease of positioning.…”
Section: Methodsmentioning
confidence: 99%
“…As a novel application of shelf arthroplasty, Willemsen et al ( 24 , 25 ) reported a patient-specific 3-dimensional (3D) printed titanium shelf implant for ACEtabular rim eXtension (ACE-X). The implant was designed according to computed tomography (CT) imaging of the pelvis and hip joints of individual dogs to optimally extend the dorsal acetabular rim and provide adequate coverage of the femoral head.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, a pilot study with experimental dogs demonstrated enhanced femoral head coverage, reduced hip laxity, and increased weight bearing by force plate analysis. Furthermore, examination of the intervened hips at 6 months post-implantation revealed normal volume and a smooth surface of both the femoral head and acetabulum cartilage, accompanied by joint capsule hypertrophy based on gross and histological assessments 17 . Upon confirmation of the efficacy and safety of the implant and treatment concept, a clinical investigation was carried out on client-owned dogs suffering from hip dysplasia.…”
Section: Introductionmentioning
confidence: 98%
“…Additive manufacturing (AM) has been introduced in the medical field in the last decade, gaining popularity specifically in the field of maxillofacial, orthopaedic, oncological and spine surgery. [1][2][3][4][5][6][7][8][9][10] The availability of materials and printers has led to lower costs of patient-specific threedimensional (3D) implants in human medicine bringing them also within the scope of the veterinary field. 11 The use of individualized implants is the latest development in implant technology and offers a wide variety of opportunities and applications.…”
Section: Introductionmentioning
confidence: 99%